Aspects of the ecology and management of small mammalian predators in northern New Zealand - Gillies, Craig (ResearchSpace@Auckland, 1998)
Each chapter in this thesis has been written as a separate paper intended for later publication. Rather than write one summary, an abstract for each chapter has been given in the order they are presented in the thesis. Chapter I. The prey species of domestic cats (Felis catus) in two suburbs of Auckland city, New Zealand. The prey brought in by 80 cats (Felis catus), over a year was monitored in two suburbs of Auckland New Zealand. The survey technique followed that of Churcher & Lawton (1987) where cat owners were asked to record (and if possible keep) the prey their cats brought in. The results for the year indicated that there were distinct differences in the type of prey taken by cats in each area. Rodents were the most important prey brought in by domestic cats in an urban / forest fringe habitat and invertebrates were the main prey brought in by domestic cats in a fully urban habitat. Birds and lizards were the second and third most important prey groups in both study areas. Rat and mouse snap trap indexes which were run at each study location, did not detect rodents in the urban habitat. The results from the urban/forest fringe concurred more with studies of feral cat diet in New Zealand whilst those from the urban area compared more to studies of domestic and stray cat diet in urban areas overseas. There were seasonal trends in the prey captured in each area and in both areas cats hunted less over the winter months. Chapter II. Diets of coexisting alien mammalian carnivores in Northern New Zealand. 120 feral cats, 85 stoats (Mustela erminea), 28 weasels (M. nivalis) and 16 ferrets (M. furo) were caught over three years, in Northland, New Zealand. The gut contents of these animals were examined and their food habits described. The main prey groups of cats were (in order of importance by weight), lagomorphs, rodents (Rattus spp & Mus musculus), other mammals, birds and invertebrates. The main prey of stoats were rodents, birds, lagomorphs, skinks (Cyclodina spp) and invertebrates. Skinks, followed by mice, were the main prey of weasels. Rabbits (Oryctolagus cuniculus) were the most commonly occurring prey item in the ferret guts. The food habits for cats and stoats were compared between different habitats within the Northland region where these animals were collected from. There was little difference between habitats, but invertebrates occurred more frequently and lagomorphs less frequently in the diet of animals from forest habitats compared to those from forest / pasture and coastal habitats. No differences were found in the prey of male and female cats, but invertebrates occurred more frequently in the guts of sub-adult cats compared to adult cats. Skinks occurred more frequently in the guts of female stoats, which tended to take smaller prey items than males. Chapter III. Home range of introduced mammalian carnivores, feral cats (Felis catus), stoats (Mustela erminea) and a ferret (M. furo) at Trounson Kauri Park, Northland, New Zealand. The minimum home ranges of eleven feral cats, four stoats and one male ferret were examined by radio telemetry at Trounson Kauri Park in Northland New Zealand. The average minimum home range of male feral cats was 305 ± 74ha. This was not significantly larger than the 122 ± 35 ha minimum average home range of female cats. The minimum average home range of three male stoats was 108 ± 19 ha and the minimum home range of one female stoat was 50 ha. The male ferret had a minimum home range of 179 ha. There was no overlap spatially, in the home range of three adult male cats. There was also very little spatial overlap in the home range of four female cats. There was substantial home range overlap with four sub-adult male cats. The home ranges of these sub-adult male cats also overlapped spatially with those of the adjacent females and adult males. The home ranges of two male stoats overlapped spatially to some degree and the home range of another male stoat overlapped that of the female stoat substantially. The home range of the male ferret overlapped the home ranges of all of the cats occupying similar areas of the park. The home ranges of two male stoats overlapped the home ranges of the adjacent cats but not into the "core" areas of those cats ranges. Chapter IV. Secondary poisoning of introduced mammalian carnivores during possum and rodent control operations at Trounson Kauri Park, Northland New Zealand. Predatory mammals were monitored by radio telemetry through a 1080 then brodifacoum poison baiting operation at Trounson Kauri Park in Northland, New Zealand to target possums (Trichosurus vulpecula) and rodents (Rattus rattus, Rattus norvegicus & Mus musculus). All six feral cats (Felis catus), and the single stoat (Mustela erminea) and ferret (Mustela furo) being monitored at the beginning of the operation died of secondary poisoning following the 1080 operation. A further two cats and four stoats were radio tagged and monitored through the ongoing poisoning campaign using brodifacoum in a continuous baiting regime. None of these radio tagged carnivores died of secondary poisoning. However, tissue analysis of additional carnivores trapped at Trounson found that cats, weasels (Mustela nivalis) and to a lesser extent stoats did contain brodifacoum residues. The duration that the radio tagged predators were alive in and around Trounson Kauri Park suggested that the secondary poisoning effect was much reduced under the continuous baiting strategy, compared to the initial 1080 poison operation. Chapter V. Managing alien mammals in mainland New Zealand: The implications for predator/prey interactions in complex communities. Recent advancements in alien pest mammal control technologies have enabled conservation managers to attempt long term, large scale, predator and browser control programmes at mainland sites in New Zealand. At Trounson Kauri Park (in Northland, New Zealand) feral cats, ferrets, stoats and weasels plus rodents and possums were controlled for two and a half years. Early results from Trounson suggested that some native birds and plants responded positively and quickly to the control of these alien pest mammals. However, the management also affected the predator-prey and predator-predator interactions, within the mammalian community, with changes in the predator guild and some prey species increasing in abundance. The long term effects of these responses within the mammalian community to control efforts are unclear. A review of the international literature served only to confirm the view that managing alien mammals where re-invasion is constant will be a complex task. Conservation management at mainland sites like Trounson Kauri Park, may in effect be acting as crude mammalian predator removal experiments. Monitoring changes in predator-prey interactions and predator-predator interactions at this and other intensive management sites over sufficient time frames could provide scientists with the critical ecological data required to construct useful predictive models. The ability of managers to target specific pests at critical times would represent a significant advancement in controlling predatory mammals on the New Zealand mainland.